EFFECT OF PRUNING AND POP SUPERNASA FERTILIZER APPLICATION ON GROWTH AND YIELD OF MELON (Cucumis melo L) - Nursah Basuki; Ansoruddin Ansoruddin; Sri Susanti Ningsih (Bernas : Jurnal Penelitian Pertanian, 2018)
This research was conducted in Sirsak Street, Kisaran Timur Village, Asahan District, North Sumatra. Flat Topography, height  25 m asl, and coordinate point 203'-326' North Latitude and 991'-1000' East Longitude. The experiment was conducted in May ― July 2017. This research is based on the Randomized Block Design (RBD) factorial with 2 factors and 3 replications. The first factors was the pruning of 3 levels P0 = Control (no pruning), P1 = pruningand leaving 6 branch ( 7, 8, 9, 10, 11, and 12), P2 = pruning and leaving 4 branch ( 7, 8, 9 and 10). The second factors is application of POP Supernasa fertilizer with 4 levels S0 = Control ( 0 ml/l water/block), S1 = 20 ml/ 10 L water/block, S2 = 40 ml/ 10 L water/block, S3 = 60 ml/ 10 L water/block. The result of research that pruning P2 = pruning and leaving 4 branch ( 7, 8, 9 and10), the best production contained is the parameter diameters of fruits 18,01 cm and production/plant 4,11 kg. Applications of POP Supernas S3 = 60 ml/ 10 L air/plot, the best production contained is the parameter flower emergence 19,33 day, fruit emergence 23,33 day, fruit diameters 17,97 cm and productions 4,10 kg/ plant. The interactions pruning and POP Supernasa application on growth and yield of melon showed no significant effect on all parameters was observed.